THE EFFECT OF CREDIT COLLECTION PRACTICES ON FINANCIAL PERFORMANCE OF MANUFACTURING FIRMS IN KENYA - Cheptum, Florence Jemutai (International Journal of Finance and Accounting, 2019)
Purpose: The main objective of this study is to establish the effect of credit collection practices on the financial performance of manufacturing firms in Kenya. Manufacturing firms have been experiencing a number of challenges in their application of credit collection practices to ensure sound financial performance. Methodology: The study adopted two research designs; descriptive and causal. The accessible population for the study was 558 registered manufacturing firms. Stratified sampling technique was used to select the sample size and a sample of 233 manufacturing firms was arrived at using Yamane's formula. Questionnaires were the main instruments used to collect primary data. Both descriptive and inferential statistics were utilized in data analysis with the aid of SPSS. Data presentation methods used included frequency tables and percentages. Data collected were tested using, univariate test to provide an insight using both parametric (F-test) and non-parametric test (Pearson correlation coefficient). Multivariate analysis was also carried using the multiple regression analysis which indicated the level of the relationship that existed between the independent variables and the dependent variable. Results: Findings indicate that the credit collection practices have a significant positive effect on the financial performance of the manufacturing firms (p<0.05). This can be attributed to the fact that owners of manufacturing firms have the ability to control and manage credit through their experienced and skilled credit managers. In conclusion, credit collection practices positively and significantly affected the financial performance of the firms. Unique contribution to Theory, Practice and Policy: The study recommends that registered manufacturing firms operating in Kenya should adopt credit collection practices since it positively and significantly affects the financial performance. This can be achieved by setting techniques which are used to collect credit and this helps in reducing chances of credit defaults.